2018
DOI: 10.1186/s12891-018-2148-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of perioperative complications for posterior spinal fusion in degenerative scoliosis patients: a retrospective study

Abstract: BackgroundsRare study has been conducted to detect risk factors of perioperative complications, which are closely related to preoperative status of the patients and surgical stress. The aim of this study is to detect these relationships in degenerative scoliosis (DS) patients.MethodsPerioperative complications of 226 cases with DS (56 males and 170 females; 65.5 ± 8.1 years old), who accepted posterior fusion in our hospital from January, 2013 to July, 2017, were retrospectively reviewed. Potential risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
11
1
1
Order By: Relevance
“…The incidence of perioperative complications in our study (13.4%) was less than what was reported in a previous study (19.5%) [18]. Additionally, coronal and sagittal imbalance is more common in degenerative scoliosis than in non-degenerative adult scoliosis [4].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The incidence of perioperative complications in our study (13.4%) was less than what was reported in a previous study (19.5%) [18]. Additionally, coronal and sagittal imbalance is more common in degenerative scoliosis than in non-degenerative adult scoliosis [4].…”
Section: Discussioncontrasting
confidence: 71%
“…Owing to the fact that most of our patients were fairly young, there was relatively little data on history of lumbar operation, previous medication use, or whether there were any age-associated comorbidities such as diabetes and osteoporosis, some of which could be potential risk factors for ADS. Several studies have reported a direct correlation between parameters such as the ASA grade, Cobb angle, total operation time, PT, level of fusion, length of hospital stay, staging, multiple surgeries and the incidence of perioperative complications in ADS [9,18,[24][25][26]. However, further research is needed to identify the risk factors for perioperative complications in adult non-degenerative scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Extended operative time is a known factor correlating with postoperative complications in elderly patients undergoing lumbar spine surgery and patients with degenerative lumbar scoliosis. 19,90,91 In adult spinal deformity surgery, operative time was more predictive of surgical outcomes than operative complexity (ie, increased levels fused, presence of interbody fusions, osteotomies, and pelvic fixation). 47 Procedural time in excess of 309 minutes was associated with increased complication development for patients with spinal arthrodesis analyzed from NSQIP between 2005 and 2010.…”
Section: Surgical Risk Assessmentmentioning
confidence: 99%
“…Owing to the fact that most of our patients were relatively young, there was relatively little data on history of lumbar operation, previous medication use, or whether there were any ageassociated comorbidities such as diabetes and osteoporosis, some of which could be potential risk factors for ADS. Several studies have reported a direct correlation between parameters such as the ASA grade, Cobb angle, total operation time, PT, level of fusion, LOS, staging, multiple surgeries and the incidence of perioperative complications in ADS [9,[19][20][21][22]. However, further research is needed to identify the risk factors for perioperative complications in adult non-degenerative scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were divided into two groups based on whether they had any perioperative complications: without perioperative complication group (125) and with perioperative complications group (21). The results of univariate analysis investigating the relationships between baseline/ surgical characteristics and perioperative complications are shown in Tables 1 and 2.…”
Section: Univariate Analysismentioning
confidence: 99%